Svalbard’s Haunted Landscapes - Kinossian, Nadir (Nordlit, 2020)
Cultural landscapes represent social structures, interests, and values. At the same time, the observer can derive, interpret, reinterpret, and inscribe new meanings to the landscape. Landscapes that are saturated with ideologically charged symbols dictate to the viewer what can and cannot be seen and derived from them. On the other hand, landscapes that are abandoned, ruined, partly erased, and deprived of actors, activities, and political context present a different sort of setting. What can be derived from them? What or whom do they represent? Can the current conceptualisations help to capture their meanings? This paper attempts to expand the debate on cultural landscapes, by exploring the linkages to the concepts of haunting and ghosts. It uses the Russian settlements of Barentsburg, Pyramiden and Grumant, located in Svalbard (Norway), as an example. The paper argues that ruined and abandoned landscapes are ‘haunted’, and that the viewer can engage with a haunted landscape through interactions with ‘ghosts’ – fictitious agents that fulfil two roles: i) allowing the viewer to associate with the ghost, and ii) reminding the viewer of the bygone actors, forces, and contexts that shaped the landscape.